Design and development of the income measures in the European social surveys - Hoffmeyer-Zlotnik, Jürgen H. P. (Metodološki zvezki, 2015)
In social surveys "total net household income" is an indicator of the re-spondent's socio-economic status. It describes the economic situation of household members and their positions in an income distribution. It is used as an explanatory variable in mobility studies and as a social-demographic background item in inequality research. This paper shows the impact of questionnaire design on measurements of "total net household income" in social surveys. In particular we illustrate how the measurement quality of the income variable depends on the data sources about the national income distributions used to design the answer categories offered to the respondent. Beginning with the fourth round of European Social Survey fielded in 2008 and the following years, the income categories for the question about the "total net household income" amount are built on national income distribution of households resident in the country under study. The response categories of the modified ESS questionnaires have been based on deciles of the actual household income distribution in the country in question. The central organizers of European Social Survey (ESS) instruct the national questionnaire designers to define the income brackets for the answer categories using the deciles of the most reliable national income data source. Analyzing the ESS data from 2008, 2010 and 2012, we found in some countries remarkable divergences from the expected 10% frequencies in each category. In this article we argue that the quality of this new income measure depends on the quality of the reference statistics from which the national household income ranges are derived. The quality of the responses to the survey question about the "total net household income", and finally the quality of the obtained survey measure, depends on the quality of the reference statistics from which the household income categories for the answers is derived. These reference data must cover all types of the household's income from all household members and optimally represent the na-tional distribution of household income across the survey universe. That means first that all possible payments accruing to a household and all its members in a given country must be reported in references, and second that all households in the survey's universe must be represented in the statistics used to detect the answer categories. Then the income brackets for the response categories can be calculated using the 10% percentiles from the income distribution in the reference data. Relevance, accuracy, timeliness, comparability, coherence, accessibility and clarity are quality domains of official statistics used as reference data for the survey measurement. We conclude that the central coordinators of the ESS define and communicate minimum threshold values for quality domains of the reference data. The national coordinators should report deviations. This would give the users of ESS data an insight into the quality of the income measurement.
Keywords: Statistics; Statistika; Družboslovne ankete; Social surveys; družboslovno raziskovanje; dohodek; merjenje